Ways to Prevent Road Traffic Accidents - Isoxanov Utkir (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article analyzes the role of road traffic accidents (RTAs) as a pressing issue on both global and national scales. The main causes of RTAs are categorized into four groups: driver-related, technical, infrastructure-related, and organizational-legal factors. Furthermore, the article presents five primary approaches to reducing RTAs: improving legislation, modernizing infrastructure, implementing technical inspections and digital tools, enhancing education and training, and developing medical and rescue services. The advanced experiences of Sweden, the Netherlands, and Japan are cited as examples. Specific recommendations for Uzbekistan are developed, including adopting the “Vision Zero” strategy, repairing roads, reforming driving schools, and expanding the emergency medical services network.